Value systems of Malay and Chinese managers: a comparative study - Nik A. Rashid Ismail (Penerbit Universiti Kebangsaan Malaysia, 1982)
Among basic psychological variables values has been a strong influential force on managers. This study explores the system of work values of Malay and Chinese managers. The findings indicate that Malay managers were much more egocentric and sociocentric compared to Chinese managers, who on the other hand, were much more conformist. However, both groups did not differ significantly on tribalistic, manipulative and existential values.